Optimalisasi Pemasaran UMKM Dalam Meningkatkan Jiwa Wirausaha di Kalangan Pemuda Desa Cijulang Kecamatan Cijulang Kabupaten Pangandaran - Nupusiah, Ulpah; Kamaludin, Kamaludin; Putra Hani Pitriyani; Gunawan, Gunawan; Predi Supriadi; Yayat Hidayat; Irpan Ilmi (Jurnal Insan Pengabdian Indonesia, 2024)
The development of the times, especially in this digital era, requires MSME actors to be able to compete in marketing their products. The problems faced are still many MSME actors who lack knowledge and do not keep up with developments in the technological era. The purpose of this community service is to improve digital marketing and foster an entrepreneurial spirit among youth so that they are able to compete in increasing the level of the economy. This research uses the PAR method ((Participatory Action Research). The community service activities carried out are very beneficial for participants in increasing their knowledge and utilization of digital media as a means for product marketing, thus providing great opportunities within the reach of market share which can impact on income turnover. Community service in the form of seminars on optimizing MSME marketing in increasing the entrepreneurial spirit among youth is urgently needed because of the development of the technological era which requires MSME actors to compete globally with the online marketing system, this is where the role of youth is needed to bridge and deal with this development with an in-depth understanding of the utilization digital media.